2017
DOI: 10.3389/fpls.2017.00562
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Plant Uptakes for Water, Nutrients, and Oxygen Are Not Always Met by Irrigation Rate and Distribution in Water-based Cultivation Systems

Abstract: Growing on rooting media other than soils in situ -i.e., substrate-based growing- allows for higher yields than soil-based growing as transport rates of water, nutrients, and oxygen in substrate surpass those in soil. Possibly water-based growing allows for even higher yields as transport rates of water and nutrients in water surpass those in substrate, even though the transport of oxygen may be more complex. Transport rates can only limit growth when they are below a rate corresponding to maximum plant uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 71 publications
0
33
0
1
Order By: Relevance
“…Water flow rate is an important factor that determines water and nutrient availability in the root zone, thus influencing crop growth in hydroponic systems [25]. However, only limited information is available regarding water flow rate for aquaponic crop production.…”
Section: Flow Rate Affects Water Quality In Aquaponic Systemsmentioning
confidence: 99%
“…Water flow rate is an important factor that determines water and nutrient availability in the root zone, thus influencing crop growth in hydroponic systems [25]. However, only limited information is available regarding water flow rate for aquaponic crop production.…”
Section: Flow Rate Affects Water Quality In Aquaponic Systemsmentioning
confidence: 99%
“…Moreover, the concentration of these cations in the soil also varies with the type of vegetable cultivated because the nutrient uptake and accumulation varies with the vegetable type [ 4 , 115 ]. Vegetables are reported to be a rich source of nutrients and are capable of up-taking cations (Na, K, Ca, and Ba) in high quantities compared to crops and plants.…”
Section: The Effect Of Wastewater On the Physico-chemical Propertimentioning
confidence: 99%
“…Several studies reported that bacteria can bind to sand particles and roots during sedimentation in wastewater treatment processes and form settable solid compounds. In addition, larger particles have a higher sedimentation rate (33). It means that the bottom layer of CW, settles coliforms particularly total and fecal coliforms such as E. coli, Streptococci, and Enterococcus, by precipitation mechanism (34).…”
Section: Discussionmentioning
confidence: 99%